POSSIBLE CHANGE OF HYDRODYNAMIC CONDITIONS OF NOVOSELTSOVO SPRING WATERS UNDER THE INFLUENCE OF DEPOSIT USE IN THEIR VICINITIES (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
On the basis of analysis and generalization of available data, we have come to conclusion, that the further operation of basalt deposit is inadmissible, as it is located in the second sanitary-protective zone of Novoseltsovo springs and can influence a hydrodynamic mode of these springs. This inadmissible, because in the present waters of springs with 370 L/s expense are used as drinking water supply nearby 150000 inhabitants of settlements.
Keywords: Novoseltsovo spring; basalt deposit; sanitary-protective zone